Exploration of Bacteria in Red Chili Plant Soil with Potential as Plant Growth Promoting Rhizobacteria (PGPR) - Miladiarsi Miladiarsi; Muhammad Rizal; Padil Wijaya (Acta Solum, 2025)
Soil fertility depends on the availability of sufficient nutrients for plant absorption. Chemical fertilizers can be used to provide sufficient N and P, but this affects soil health. The presence of rhizobacteria act as biofertilizers by increasing nutrients and altering soil formation, especially in the phosphate and nitrogen cycles. Phosphate-solubilizing and nitrogen-fixing bacteria play a role in increasing soil fertility and improving unstable soil properties. This study aims to identify rhizobacteria that have the potential as PGPR to increase N and P levels in the soil. Soil samples were collected randomly at a depth of 10 cm around chili plant roots. Bacteria were isolated using serial dilution and cultured on Pikovskaya medium. A total of 27 isolates produced clear zones with the highest solubility index and were inoculated on Nitrogen-Free Bromthymol Blue Agar (NFB) to evaluate N fixation through a color change from green to blue, as well as hypersensitivity tests on tobacco plants. Isolates showing the highest P solubility, highest N fixation ability, and no necrosis in tobacco were inoculated into sterile soil to analyze compound changes. Soil N content was measured using the Kjeldahl method, while phosphate levels were analyzed using the Bray I and HCl methods. The results of the study showed that the addition of KE2.15 isolate to the soil after 4 weeks of application increased the total organic N and available P content, making it a potential biofertilizer.